MENGGALI AKAR MASALAH: Analisis Kasus Perceraian di Indonesia - Januari, Nia (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
Divorce has become an increasingly deepening social issue in Indonesia, with divorce rates continuing to increase in recent years. These issues have a significant impact on individuals, families, and society as a whole. Therefore, this research aims to dig deeper into the factors that influence the divorce rate in Indonesia. This research uses a qualitative approach. Qualitative data was obtained through interviews with individuals who had experienced divorce as well as literature reviews involving case studies. The results of this research identify several main factors that contribute to the divorce rate in Indonesia, including conflict within the household, economic factors, and social change. The impact of divorce includes psychological problems for individuals, changes in family dynamics, and increased economic burden. This research also produces policy recommendations that include strengthening marriage education programs, improving support systems for couples experiencing conflict, and expanding access to divorce counseling.